Gambaran Derajat Grit Pada Mahasiswa Akademi Keperawatan â€œXâ€ di Kabupaten Kepulauan Aru - Roseilla Nora Izaach (Humanitas (Jurnal Psikologi), 2017)
This study aimed to describe the level of grit in the Nursing Academy student X in the Aru Islands. Grit is the one of the latest theory in the study of Positive Psychology which emphasizes of two important aspects are perseverance of efforts and consistency of interest, that determines the success of individuals in achieving their life goals. The goal of achieving future success through education is the reason this research is conducted. Respondents in this study were students in 2014. The number of respondents are 51 people with entirely female. Measuring instrument used in this study was grit scale consists of 12 items with reliability of 0.85 and a validity coefficient range Â from 0.44 to 0.82 ( Duckworth, et.al.,2007) . Based on the results of the processing of descriptive data, it was found that the majority of respondents have a low level of grit with percentage of 86.3%. Variable aspect of grit perseverance of efforts, the majority of respondents have a low level of 90.2%, and the consistency aspect of interest, the majority of respondents have a high level of 66.7%. The socioeconomic status of the students is based on the type of work of the parents, not indicating the tendency to be related to the degree of grit. Further research that can be done is to investigate more deeply about the contribution of personality factors, differences in cultural background and demographics that affect grit.Â Keywords: Grit, socioeconomic status, demographics